Exploring Teachers’ Questioning Strategies in an EFL Classroom Interaction: A Case Study of A Vocational High School - Dian Rizki Lestari; Dewi Puspitasari (Faculty of Social and Political Sciences University of Bangka Belitung, 2022)
Teachers have a vital role in facilitating students' learning journeys. Therefore, they must carefully select and employ effective techniques during their instructional sessions. Among these techniques, questioning stands out as a particularly influential method. This study focuses on exploring the utilization of questioning strategies by English teachers in the context of EFL (English as a Foreign Language) classroom interactions within Vocational High Schools. The research adopts a case study approach, centering around one EFL teacher as the participant. Data collection involved interviews and observations, while Miles and Huberman's qualitative data analysis framework was applied for data interpretation. The findings of this study indicate that, among the four question types outlined in Wangru's (2016), the teacher predominantly employs two strategies during classroom interactions: prompting and repeating. In contrast, probing and redirecting strategies are used less frequently. The questions posed by the teacher cover a range of topics, including material-related inquiries and those aimed at eliciting student responses. Consequently, students engage actively in the learning process, leading to skill enhancement. In conclusion, this research demonstrates that effective employment of questioning strategies contributes to an interactive learning environment.